I'm on it! - Tsurumi, Andrea (Hyperion Books for Children, 2021)
"When Frog and Goat turn a simple game into an all-out competition, things get out of hand...until finally, they're over it"--
Keywords: Games -- Fiction; Competition (Psychology) -- Fiction; Goats -- Fiction; Frogs -- Fiction; Humorous stories; Readers